1974
DOI: 10.1042/cs0460419
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm of the Total Hydroxyproline: Creatinine Ratio in Urine

Abstract: Circadian rhythm of the total hydroxyproline: creatinine ratio in urine C. A. MAUTALEN, Instituto de Investigaciones Medicas, Buenos Aires, 24 October 1973.In a recent paper in Clinical Science Dr Wharton et al. (1973,44,(359)(360)(361)(362)(363)(364)(365) found a significant correlation of both height and weight velocities with the total hydroxyproline : creatinine ratio (THP:Cr) in random urine samples from twenty-six adolescent boys. The validity of results obtained in random samples of urine is based on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1977
1977

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…THP:Cr in 24-hour specimens of urine has been shown to be a more accurate measure of growth rate than total hydroxyproline alone (Allison et al, 1966), and further studies have shown a reasonable correlation of this ratio in random specimens with that in 24-hour collections (Howells et al, 1967;Younoszai et al, 1969). However, Mautalen (1974) has pointed out that hydroxyproline excretion and THP:Cr in adults is subject to diurnal variation and has questioned the validity of measurements on random specimens. Reviewing this controversy, Wharton (1974) noted that the variations in THP:Cr in children were small enough to make measurements on single specimens adequate for clinical purposes.…”
Section: Discussionmentioning
confidence: 99%
“…THP:Cr in 24-hour specimens of urine has been shown to be a more accurate measure of growth rate than total hydroxyproline alone (Allison et al, 1966), and further studies have shown a reasonable correlation of this ratio in random specimens with that in 24-hour collections (Howells et al, 1967;Younoszai et al, 1969). However, Mautalen (1974) has pointed out that hydroxyproline excretion and THP:Cr in adults is subject to diurnal variation and has questioned the validity of measurements on random specimens. Reviewing this controversy, Wharton (1974) noted that the variations in THP:Cr in children were small enough to make measurements on single specimens adequate for clinical purposes.…”
Section: Discussionmentioning
confidence: 99%